Using ICP-OES, SEM and Polarography Techniques to Determination of Lead and Tin in Brass alloy - Marwa Aborways; Hana Binhamad (AlQalam Journal of Medical and Applied Sciences, 2022)
Aims. The objective of this study was to analyses brass (Pb, Sn) and then make an evaluation between all the results obtained using different methods (ICP-OES, SEM and polarography) to see if these methods could obtain reliable results compared with the certified values for each element. Methods. Known sample of brass was analyzed to determine the concentration of elements (Pb and Sn), and three brass samples were collected from a shop. These samples were weighed (10 mg) and then dissolved in 1ml aqua regia solution (3:1 HCl and HNO3 respectively): after 24 hours the solutions were diluted by factor 100-200 dilution to prepare different concentration ranges. Results. In this study, it was found that, for each element of different brass samples, the calibration curves were very linear and the results obtained from this study using various methods are reproducible and have been repeated three or four times in a single lab validation. Conclusion. It can be concluded that the results of SEM were very close to compositions of each element when compared to standards. In addition, polarography method has given very good results for lead in unknown sample. Also, the tin result was very reliable; this result was not expected using different techniques, due to the small amount of tin compared with different method. The limits of detection are in the range of ppm for Pb and Sn elements for ICP-OES. Cite this article: Aborways M, Binhamad H. Using ICP-OES, SEM and Polarography Techniques to Determination of Lead and Tin in Brass alloy. Alq J Med App Sci. 2022;5(2):573-579. https://doi.org/10.5281/zenodo.7415820